Designing Mathematics Learning Media Using Adobe Animate Application at SMKN 1 Bukittinggi - Fikri, Miftahul; Musril, Hari Antoni (Jurnal Informatika UPGRIS, 2021)
To achieve the goals of education, of course, students must go through a process, namely learning by following all the series of learning processes that are expected by a teacher to create an interesting learning atmosphere, for example by utilizing learning media. Research on the design of mathematics learning media using adobe animate applications at SMKN 1 Bukittinggi uses the 4D version of the research and development (RD) method, namely Define, Design, Develop, and Disseminate. The system development model uses Luther Sutopo's Multimedia Development Life Cycle development model which consists of 6 stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. The product test used in this research is the validity test, practicality test, and effectiveness test. The results of the product test that the author did obtained a validity test from 3 experts obtained a value of 0.96 with a very valid category, the practicality test of 8 practitioners obtained a value of 0.95 with a very high category, and the effectiveness test of 11 assessors obtained a value of 0, 90 with very effective category.